Measuring Performance – Conceptual Framework Questions - Jaroslav Wagner (European Financial and Accounting Journal, 2008)
This paper aims to formulate some principal questions which should be used as start-point for design and analysis of the performance measurement conceptual framework. The paper is based on literature study followed by analysis and generalization. It reflects the diversity of approaches to performance measurement in performance-oriented literature and it investigates their similarities and differences. The paper is divided into two sections. First section defines performance measurement as a causal chain of activities and it deals with the role of subjectivity in this chain. Second section concerns common features of various performance models for organizational performance, namely motivational aspects of performance model design, users and purposes of performance information, hierarchical structure and time dimension of performance model etc.
Keywords: M41; 650; Organizational Performance; Performance Measurement; Subjectivity in Measurement